In vitro biomechanical evaluation of sagittal split osteotomy fixation with a specifically designed miniplate - Pereira Filho, Valfrido Antonio [UNESP]; Iamashita, H. Y. [UNESP]; Monnazzi, M. S. [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Vaz, Luis Geraldo [UNESP]; Passeri, L. A. [UNESP] (Elsevier, 2013)
Recent studies have evaluated many methods of internal fixation for sagittal split ramus osteotomy (SSRO), aiming to increase stability of the bone segments while minimizing condylar displacement. The purpose of this study was to evaluate, through biomechanical testing, the stability of the fixation comparing a specially designed bone plate to other two commonly used methods. Thirty hemimandibles were separated into three equal groups. All specimens received SSRO. In Group I the osteotomies were fixed with three 15 mm bicortical positional screws in an inverted-L pattern with an insertion angle of 90°. In Group II, fixation was carried out with a four-hole straight plate and four 6 mm monocortical screws. In Group III, fixation was performed with an adjustable sagittal plate and eight 6 mm monocortical screws. Hemimandibles were submitted to vertical compressive loads, by a mechanical testing unit. Averages and standard deviations were submitted to analysis of variance using the Tukey test with a 5% level of significance. Bicortical screws presented the greatest values of loading resistance. The adjustable miniplate demonstrated 60% lower resistance compared to bicortical screws. Group II presented on average 40% less resistant to the axial loading. © 2012 International Association of Oral and Maxillofacial Surgeons.
Keywords: biomechanical evaluation; rigid internal fixation; sagittal split ramus osteotomy; biomechanics; bone plate; bone screw; clinical evaluation; in vitro study; osteosynthesis; sagittal split ramal osteotomy; Biomechanics; Bone Plates; Compressive Strength; Dental Stress Analysis; Fracture Fixation, Internal; Humans; Jaw Fixation Techniques; Mandible; Models, Anatomic; Osteotomy, Sagittal Split Ramus; Polyurethanes